Mortality among Heart Failure Patients in the Presence of Cachexia - , Andrianto; Karman, Ula Nur Pramesti; Mudjanarko, Sony Wibisono; Ardiana, Meity; Hermawan, Hanestya Oky (Folia Medica Indonesiana, 2023)
Highlights: • Around 38.8% of heart failure patients with cachexia died during the 180-1,876-day follow-up period. • Cachexia increases the risk of mortality in heart failure patients. Abstract: Despite the fact that obesity has long been recognized as a risk factor for cardiovascular disease, the mortality rate of heart failure (HF) patients with cachexia is still high. Several studies have been conducted to investigate the association between cachexia and mortality in HF patients. However, the research results vary, as do the diagnostic criteria employed to assess cachexia. This meta-analysis aimed to conclusively summarize the association between cachexia and mortality in HF patients. The data were obtained from prospective or retrospective cohort studies with full texts in English or Indonesian and keywords related to